Tafsir Tematik Al-Qur'an dan Piagam Madinah sebagai Basis HAM dan Toleransi untuk Resolusi Konflik Keagamaan di Indonesia - Firdaus Fadilah Umar; Siti Badi'ah; Bukhori Abdul Somad (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
This article examines the integration of human rights (HR) and tolerance values in Islam through a thematic (maudhu’i) interpretation of Qur’anic verses combined with a historical-juridical analysis of the Charter of Medina, in order to formulate a model of religious conflict resolution in Indonesia. The study is motivated by the rise of intolerance, obstacles to minority worship, syncretism in the name of tolerance, and persecution and vigilantism that undermine national plurality. This research employs a qualitative library method with a thematic exegetical approach and sociocultural analysis of primary sources: the Qur’an, the text of the Charter of Medina, and authoritative works of tafsir. The findings show that, first, the Islamic concept of human rights rests on a theocentric paradigm (karamah al-insan) balancing rights and obligations, distinct from the Western anthropocentric paradigm. Second, the Charter of Medina reflects theocentric human rights and inclusive citizenship (ummah wahidah) consistent with the thematic interpretation of QS al-Baqarah: 256, al-Hujurat: 13, al-Kafirun: 6, al-Ma’idah: 8, al-An’am: 151, and al-Ma’idah: 32. Third, integrating both sources produces a wasathiyah paradigm that requires the state to guarantee minority worship, reject syncretism, and eradicate vigilantism through the state monopoly of law. This article contributes a revelation-based normative-practical framework to strengthen religious harmony policies in Indonesia.